2017
DOI: 10.1007/s12325-017-0556-1
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD as a Sexual Dimorphic Disease: Role of Gender and Reproductive Status in the Development and Progression of Nonalcoholic Fatty Liver Disease and Inherent Cardiovascular Risk

Abstract: Nonalcoholic fatty liver disease (NAFLD) spans steatosis through nonalcoholic steatohepatis, cirrhosis, and hepatocellular carcinoma (HCC) associated with striking systemic features and excess cardiovascular and liver-related mortality. The pathogenesis of NAFLD is complex and multifactorial. Endocrine derangements are closely linked with dysmetabolic traits. For example, in animal and human studies, female sex is protected from dysmetabolism thanks to young individuals’ ability to partition fatty acids toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
344
2
16

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(423 citation statements)
references
References 221 publications
(293 reference statements)
29
344
2
16
Order By: Relevance
“…On the contrary, postmenopausal women are known to carry a greater risk of NAFLD than men, suggesting a protective role of oestrogens. Further, the role of NAFLD as a sexual dimorphic disease is also supported by animal models that demonstrate a disposition of male individuals to more advanced fatty liver disease compared to females that is linked to a state of subclinical inflammation and increased hepatic morbidity . A study applying a computational model concluded that due to sex‐specific metabolic demands, female and male livers are metabolically diverse and therefore differently regulated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, postmenopausal women are known to carry a greater risk of NAFLD than men, suggesting a protective role of oestrogens. Further, the role of NAFLD as a sexual dimorphic disease is also supported by animal models that demonstrate a disposition of male individuals to more advanced fatty liver disease compared to females that is linked to a state of subclinical inflammation and increased hepatic morbidity . A study applying a computational model concluded that due to sex‐specific metabolic demands, female and male livers are metabolically diverse and therefore differently regulated .…”
Section: Discussionmentioning
confidence: 99%
“…A study applying a computational model concluded that due to sex‐specific metabolic demands, female and male livers are metabolically diverse and therefore differently regulated . In addition, a recent review stated that most published clinical and epidemiological studies fail to examine sex differences appropriately' and suggested to consider sex differences, sex hormones, age and other reproductive information in clinical investigation and gene association studies of NAFLD 'in order to fill current gaps and implement precision medicine for patients with NAFLD' …”
Section: Discussionmentioning
confidence: 99%
“…8 Our results extend these findings to include also basal EGP and EGP during insulin suppression. Moreover, as numerous studies have shown clear differences between sexes in lipid and FFA metabolism, and we studied only men, 14 the results cannot be extended to women. The difference, however, is probably explained by the "regression to the mean" phenomenon, as the baseline difference was abated after the intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, NAFLD is considered the hepatic manifestation of the metabolic syndrome (MS), which is a multisystem disruption of energy homeostasis primarily driven by insulin resistance (IR) . In addition, some studies have demonstrated that the prevalence of NAFLD is higher among the male population, increases with age, and varies among different ethnicities . Moreover, it has been clearly demonstrated that NAFLD is associated with an increased risk of cardiovascular disease (CVD), independent of other risk factors of CVD, such as obesity and diabetes, and CVD is the most frequent cause of death among patients with NAFLD …”
mentioning
confidence: 99%
“…Although the spectrum of NAFLD is reported to be more common in men, NASH was initially described as a liver disease of elderly women . It is known that after menopause, the prevalence of NAFLD increases compared to the premenopausal state, with rates similar to the prevalence of NAFLD in men as well as a comparable risk of progression of liver disease . Given that most of these data come from tertiary care centers or review articles, there is a paucity of data using a population‐based data set about the burden and outcomes of NAFLD in the adult female population.…”
mentioning
confidence: 99%